UTILIZING SENTANI FOLKTALES TO TEACH SPEAKING FOR CHILDREN OF COMMUNAL AGENTS IN JAYAPURA REGENCY, PAPUA - Wigati Yektiningtyas; Juwita Purnamasari Br.Ginting (Universitas Bengkulu, 2020)
Folktale is one of Sentani people’s cultural heritages that is rarely told anymore. As social products that teach knowledge, history and moral values, folktales have to be preserved. In Jayapura Regency, there are some communal agents for children that have various programs and one of them is teaching English. To keep motivating them learning, it needs more interesting and challenging materials. From the research on revitalization of Sentani language for children through folktales in Jayapura Regency in 2017-2018, it was found that children like to listen and read Sentani folktales. Accordingly, this paper aims at utilizing folktales to teach English for children focusing on speaking in some children communal agents in Jayapura Regency by exploring two main questions, i.e. (1) why teaching speaking using Sentani folktales and (2) how to teach speaking using Sentani folktales. This is a qualitative-descriptive study utilizing data of folktales that were obtained via observation, interview, and FGD from some informants, namely tribal chiefs and Sentani elders in East, Central, and West Sentani in 2017. This writing adopts theory of literature and language teaching (Lazar, 2002) and Vigotsky’s scaffolding learning (Omrod, 2020). This study concludes that (1) children are more active and enthusiastic to speak in English, (2) children are able to learn their ancestor’s heritages, (3) it is an alternative way of both revitalizing Sentani folktales and disseminating the socio-cultural values embedded in them.